2014
DOI: 10.7314/apjcp.2014.15.5.2221
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Expression of Cell Adhesion Molecules CD44v6 and E-cadherin and Lymphatic Metastasis in Non-small Cell Lung Cancer

Abstract: Objective: To explore the relationship between expressions of cell adhesion molecules CD44 v6 and E-cadherin (E-cad) and lymphatic metastasis in non-small cell lung cancer (NSCLC). Materials and Methods: Eightyseven tissue samples obtained from patients with primary NSCLC were collected in our hospital from Dec., 2007 to Dec., 2012, and the expressions of CD44 v6 and E-cad gene proteins in these samples were detected by immunohistochemical method. Results: In the tissue without lymphatic metastasis, the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Study by Sun et al elucidated that CD44v6 might be correlated with the histogenesis of NSCLC, and decreased CD44v6 expression was an adverse prognostic indicator for squamous cell carcinoma rather than adenocarcinoma or bronchioalveolar carcinoma (Sun et al, 2013). Another study found the positive expression rate of CD44v6 was significantly lower in the NSCLC tissue without lymphatic metastasis, which was accordant with our results, and detection of CD44v6 expression could be used to judge the lymphatic metastasis in NSCLC (Su et al, 2014). The mechanism of CD44v6 promoting the metastasis of cancer may be attributed to its interactions with various components of the extracellular matrix, and its involvement in cell adhesion and critical signaling pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Study by Sun et al elucidated that CD44v6 might be correlated with the histogenesis of NSCLC, and decreased CD44v6 expression was an adverse prognostic indicator for squamous cell carcinoma rather than adenocarcinoma or bronchioalveolar carcinoma (Sun et al, 2013). Another study found the positive expression rate of CD44v6 was significantly lower in the NSCLC tissue without lymphatic metastasis, which was accordant with our results, and detection of CD44v6 expression could be used to judge the lymphatic metastasis in NSCLC (Su et al, 2014). The mechanism of CD44v6 promoting the metastasis of cancer may be attributed to its interactions with various components of the extracellular matrix, and its involvement in cell adhesion and critical signaling pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in the expression of adhesion proteins can affect downstream signaling cascades and enhance cellular survival. Many tumor cells can switch on/off the expression of adhesion molecules so that they express the correct adhesion molecules in different microenvironments, thus preventing the induction of cellular death (Su et al, 2014). In this study, EDTA was used to block intercellular adhesion and osteosarcoma anoikis was found to increase.…”
Section: Discussionmentioning
confidence: 87%
“…E-cadherin was significantly related to the degree of EMT and tumor malignancy, for example in lung cancer (Bremnes et al, 2002), gastric cancer (JooRewChoi et al, 2002), skin cancer (McGary et al, 2002), breast cancer (BerxVan Roy 2001), pancreatic cancer (JooRewPark et al, 2002) and nasopharyhgeal cancer (Tsao et al, 2003). Recently, studies have demonstrated that the positive expression rate of E-cadherin in NSCLC tissue without lymphatic metastasis was significantly higher than that with lymphatic metastasis (47.2% vs. 21.6%) (Su et al, 2014). Earlier studies showed that expression of E-cadherin was associated with the patients' survival in NSCLC (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Through metastasis, NSCLC cells are easily found in the bone, adrenal glands, liver, brain and regional lymph nodes (Tsao et al, 2003). Recently, studies have demonstrated that the positive expression rate of E-cadherin in NSCLC tissue without lymphatic metastasis was significantly higher than that with lymphatic metastasis (47.2% vs. 21.6%) (Su et al, 2014). Earlier studies showed that expression of E-cadherin was associated with the patients' survival in NSCLC (Wang et al, 2011).…”
mentioning
confidence: 99%